The Influence of Product Quality and Halal Label on the Purchase Decision of Korean Skincare in Surabaya City - Tiara Aufa Rafiqi; Reza Mubarak (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Skincare can be interpreted as products intended for treating facial skin to make facial skin healthier. It is known that South Korea is the largest importer of facial care products in Indonesia. This study aims to examine the influence of product quality and halal certification on purchasing decisions of Korean skincare products in Surabaya. It employs a quantitative method with an associative approach, and the data is analyzed using statistical techniques. The findings reveal that both product quality and halal certification significantly impact purchasing decisions for Korean skincare.